2014
DOI: 10.3109/10715762.2013.871386
|View full text |Cite
|
Sign up to set email alerts
|

Radical acylation of L-lysine derivatives and L-lysine-containing peptides by peroxynitrite-treated diacetyl and methylglyoxal

Abstract: Highly electrophilic α-dicarbonyls such as diacetyl, methylglyoxal, 3-deoxyglucosone, and4,5-dioxovaleric acid have been characterized as secondary catabolites that can aggregate proteins and form DNA nucleobase adducts in several human maladies, including Alzheimer's disease, rheumatoid arthritis, diabetes, sepsis, renal failure, and respiratory distress syndrome. In vitro, diacetyl and methylglyoxal have also been shown to rapidly add up the peroxynitrite anion (k2 ~ 10(4)-10(5) M(-1) s(-1)), a potent biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 46 publications
2
14
0
1
Order By: Relevance
“…[33] The increase in chemical acetylation of lung proteins of diacetyl-treated rats described here may be connected with the fact that diacetyl has been shown in vitro to generate acetyl radicals upon reaction with peroxynitrite, and more slowly with hydrogen peroxide. [13] The diacetyl/peroxynitrite system was then reported to promote acetylation of isolated aminoacids, peptides and albumin. These data led us to postulate that post-translational chemical acetylation of proteins may contribute to enzymatic acetylation at sites where both diacetyl and peroxynitrite at inflammation are formed.…”
Section: Protein Interaction Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…[33] The increase in chemical acetylation of lung proteins of diacetyl-treated rats described here may be connected with the fact that diacetyl has been shown in vitro to generate acetyl radicals upon reaction with peroxynitrite, and more slowly with hydrogen peroxide. [13] The diacetyl/peroxynitrite system was then reported to promote acetylation of isolated aminoacids, peptides and albumin. These data led us to postulate that post-translational chemical acetylation of proteins may contribute to enzymatic acetylation at sites where both diacetyl and peroxynitrite at inflammation are formed.…”
Section: Protein Interaction Analysismentioning
confidence: 99%
“…[5,8,9] Recently, we reported that the reaction of peroxynitrite with α-dicarbonyls, namely diacetyl and methylglyoxal, in aerated phosphate buffer pH 7.4 results in the acetylation of free amino acids, peptides and proteins added to the reaction mixture. [10][11][12][13] This reaction is initiated by nucleophilic addition of peroxynitrite to the carbonyl group of the α-dicarbonyl compound yielding a peroxynitroso adduct, whose homolysis yields acetyl radicals. Dissolved molecular oxygen adds to the radical to ultimately produce acetate from diacetyl or acetate and formate from methylglyoxal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mecanismo Hipotético para a Reação de Peroxinitrito com Metilglioxal. Pelo fato de aldeídos serem mais reativos do que cetonas, espera-se que a rota 1 seja predominante 99 .…”
Section: Hipótese De Trabalho Com Metilglioxalunclassified